2019
DOI: 10.3389/fendo.2019.00129
|View full text |Cite
|
Sign up to set email alerts
|

Factitious Cushing's Syndrome: A Diagnosis to Consider When Evaluating Hypercortisolism

Abstract: Factitious Cushing's syndrome is exceptionally rare. The diagnosis is challenging due to the interference of exogenous corticosteroids with cortisol immunoassays. We present a case of a 26 year old female that presented with clinical and biochemical features of Cushing's syndrome. She denied any exogenous corticosteroid use. She had a suppressed ACTH level with normal adrenal glands on CT scans. There was a paradoxical increase of cortisol with a 100% rise in 24 h urinary free cortisol (UFC) during the Liddle'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Skin biopsy is generally unnecessary, because the diagnosis is easy, especially for an expert eye. A history of depression is reported in many cases of factitious CS, but psychiatric evaluation can be negative or demonstrate only mild personality disorders as in our patient (9). On the other hand, anxiety, major depression, and bipolar disorders are frequently observed in patients with endogenous CS (4).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Skin biopsy is generally unnecessary, because the diagnosis is easy, especially for an expert eye. A history of depression is reported in many cases of factitious CS, but psychiatric evaluation can be negative or demonstrate only mild personality disorders as in our patient (9). On the other hand, anxiety, major depression, and bipolar disorders are frequently observed in patients with endogenous CS (4).…”
Section: Discussionmentioning
confidence: 72%
“…In many cases, steroids measurement by LC-MS/MS allowed a correct diagnosis, but it followed invasive, expensive, and sometimes unnecessary procedures. For instance, the investigation included adrenal scintigraphy, inferior petrosal sinus sampling, PET, or finally NR3C1 gene sequencing, in some patients ( 6 , 9 , 10 , 13 ). The physicians should be aware that the risk of misdiagnosis in presence of incidentally discovered pituitary or adrenal masses could be very high, especially if the HPA axis is not suppressed, but also that pituitary function can be impaired by high doses of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…It usually presents with an atypical presentation not supported by the clinical examination including physical examination, laboratory test, or imaging 11 . Patients with factitious illnesses tend to produce physical or psychological symptoms intentionally for internal incentives and to receive medical attention 4 . Clinical features of the factitious disorder are diverse, but most documented cases are women under the age of 30 who have a generally stable social life and work in or have access to the healthcare field, have a high rate of substance addiction, and have mood or personality disorders 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Maria M Pineyro et al conducted a literature review of 23 patients with factitious CS and found that 82% were female with a median age of 37 years old. Among them, 57% had a history of psychiatric disorders, and 43% had contact with the medical field 4 . A summary of the previously reported cases in the last 10 years is listed in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation